Legal Protection for Football Broadcasting License Holders Against Illegal Streaming in Indonesia - George Muhammad Maulana Helmy Gozali; Muhammad Zahran Al-Gibran; Sabili Casba Arrusd; Ikhwan Aulia Fatahillah (Anthroposia: Journal of Social and Human Development, 2026)
This study examines the legal protection available to football broadcasting license holders against illegal streaming practices in Indonesia through a normative juridical approach. The research relies on primary legal materials consisting of Law Number 28 of 2014 on Copyright, Law Number 32 of 2002 on Broadcasting, Government Regulation Number 36 of 2018 concerning the Registration of Intellectual Property Licensing Agreements, and other relevant regulations, complemented by scholarly literature and doctrinal studies. The analysis demonstrates that football broadcasting licenses possess a legally protected position within the framework of copyright and related rights, granting license holders authority to commercially exploit broadcasting content and to seek legal remedies against unauthorized retransmission. Illegal streaming constitutes an infringement of economic rights and neighbouring rights while simultaneously violating broadcasting regulations governing the dissemination of audiovisual content. Existing protection mechanisms include preventive measures through license registration, regulatory supervision, and public legal awareness, as well as repressive measures through civil litigation, criminal prosecution, and alternative dispute resolution. The findings indicate that Indonesian law provides a relatively comprehensive normative framework, although challenges associated with digital technology, platform accountability, and enforcement effectiveness continue to affect the practical realization of legal protection. Strengthening institutional coordination and adaptive digital governance remains essential for improving future protection.